Nonlinear vibration based modeling for damage detection of reinforced concrete beams / Muhammad Usman Hanif - Muhammad Usman , Hanif (2018)
Civil engineering structures, especially the bridge structures, are continuously exposed to dynamic loading, thereby deteriorating before their prescribed design life. The demographics of the civil infrastructure majorly consist of reinforced concrete structures. Out of these existing structures, one-third of these structures are structurally deficient. The conventional damage assessment techniques are time consuming and resource intensive, and cannot cater the current bridge inventory to be monitored. Therefore, the structural health monitoring paradigm in civil engineering is in need of an efficient, economical, generally applicable and a realistic global damage detection method. The research on damage detection methods carried out in the past uses vibration characteristics for damage detection. Most of the work assumes the vibrations to be linear i.e. the natural frequencies of the structures are not dependent on the amplitude of vibration. These methods are efficient and attractive for field testing, but they need the baseline data for structural condition assessment. These baseline data are usually obtained through model updating by calibrating the stiffness to match natural frequency, which ignores the intrinsic nonlinearity of the structures. The aim of this research is to propose a damage detection procedure which incorporates the mechanical behavior of concrete in modeling the nonlinearities in a realistic and efficient way. This study presents a concrete modeling framework using concrete damaged plasticity approach. This modeling framework reproduced the vibration behavior of damaged RC beams. The nonlinear behavior, in the form of nonlinear vibration characteristics, was used in proposing a damage detection algorithm which doesn’t rely on the baseline data of the structure. The model was implemented in modeling an RC beam using FE modeling software ABAQUS. An incremental static loading was applied on the beam in 10 cycles of constant intervals to induce damage up to the ultimate load capacity of the beam. Harmonic excitation was applied on the FE model to obtain changes in modal stiffness and changes in nonlinear behavior by the appearance of super-harmonics in frequency domain. It was found that the change in modal stiffness and the nonlinearity coefficients, obtained from super-harmonics, is more sensitive to damage as compared to the natural frequency reduction. These results were validated experimentally. Furthermore, the nonlinear characteristics were developed and used in proposing a damage detection method which does not rely on the baseline data of the structure. Based on the finite element model, a 3-parameters relation was proposed. The parameters of damage, nonlinearity coefficient and exciting force can be used to detect unknown damage from the known values of the excitation force and the nonlinearity coefficients from the actual structure. Therefore, the proposed methodology presents more realistic structural mechanisms, efficient modeling and sensitive damage detection approach in reinforced concrete structures.